THE IMPLEMENTATION OF SURVEY, QUESTION, READ, RECITED, AND REVIEW (SQ3R) METHOD TO INCREASE STUDENTS’ READING COMPREHENSION (An Experimental Study at the First Year Students of SMP Negeri 1 Mila) - Mustakim Sagita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2019)
The aim of this study is to discover the effect of applying SQ3R method in reading comprehension. Experimental research design is used as the research method. This research took place at SMPN 1 Mila. There was1 class chose as the sample with 24 students in class. The class was taught by using SQ3Rmethod.The instrument used to collect the data was a set of multiple choice tests, which divided as pre test and post test. The result of the research was analyzed by using t-test formula. The result showed that post -test was higher than pre-test Key Words: reading, SQ3Rmethod.